Think About It: FMR1 Gene Mosaicism. (September 2014) - Bonarrigo, Francesca Andrea; Russo, Silvia; Vizziello, Paola; Menni, Francesca; Cogliati, Francesca; Giorgini, Valentina; Monti, Federico; Milani, Donatella
Fragile X syndrome (FXS) is one of the most frequent causes of mental retardation, intellectual disability, and autism. Most cases are the result of an expansion of the CGG trinucleotide repeat in the 5′ untranslated region of the FMR1 gene and the subsequent functional loss of the related protein. We describe the case of a 4-year-old boy who clinically presents mild psychomotor delay without any major clinical dysmorphisms. Molecular analysis of the FMR1 gene showed mosaicism in terms of size and methylation, with one normal and 1 fully mutated allele, which is very rare in this syndrome. Physicians should therefore consider a diagnosis of FXS even if the patient's phenotype is mild. Although rare, diagnosing this condition has important consequences for the patient's rehabilitation and the family planning of parents and relatives.